ANALYSIS OF FORCE DISTRIBUTION PATTERN UNDER THE FORE-FOOT IN PATIENTS WITH HALLUX VALGUS DEFORMITY - Saba Eshraghi; Ibrahim Esat (European Scientific Journal, ESJ, 2015)
The purpose of this paper is to study the force pattern distribution under the fore-foot areas with and without Hallux Valgus deformity. Hallux Valgus (HV) is one of the most common foot deformities. Plantar force pattern in HV patients has been widely studied in previous published papers to identify HV condition according to their plantar force pattern. This condition occurs by the ratio of two to one women to men. People with HV have altered pressure pattern. As 23% of people develop such condition, studying and understanding the plantar force pattern is essential. Furthermore, speed of walking has an effect on force changes under the foot. So in order to examine the effect of different walking speeds on plantar force pattern, twenty people ten with and ten without HV took part in the test by walking on the pressure mat. The results showed that the variability in force pattern in the same individual was significant from one trial to another which can be concluded that obtaining consistent force pattern is an issue to overcome. After getting consistent force readings, it was observed that the higher load was under the 2nd and 3rd metatarsal heads in people with HV which was significantly different from non-HV participants. There are contradictory opinions in previous published papers on plantar pressure pattern as a means of identifying HV. Furthermore, analysing force pattern is a hurdle to overcome. As walking speed has significant effect on plantar pressure patterns, the study of this issue is badly needed.